2016
DOI: 10.1007/s00339-016-0244-z
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of P3HT:tributylphosphine oxide-capped CdSe nanocomposites

Abstract: The optical properties of nanocomposite layers prepared by incorporation of tributylphosphine oxide (TBPO)-capped CdSe nanocrystals (NCs) in a P3HT polymer matrix are studied using different nanocrystal concentrations. Reflection spectra analyzed through Kim oscillator model lead to the determination of optical constants such as refractive index n, extinction coefficient k, dielectric permittivity e and absorption coefficient a.Using the common Cauchy, Drude-Lorentz, Tauc and single-effective-oscillator theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The capping agent is then substituted with a smaller ligand such as pyridine upon formation of a more optically efficient hybrid system [17]. Recently, we have shown that the fabrication of the less bulky TBPO-capped CdSe and ZnSe nanoparticles-organic polymer hybrid system does not require the capping agent substitution step, yielding comparable efficiency to that containing pyridine as the surfactant [18,19]. As some metal complexes could be used as single source precursors for the preparation of such nanoparticles, the synthesis and investigation of the chemistry of new related metal complexes would be of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…The capping agent is then substituted with a smaller ligand such as pyridine upon formation of a more optically efficient hybrid system [17]. Recently, we have shown that the fabrication of the less bulky TBPO-capped CdSe and ZnSe nanoparticles-organic polymer hybrid system does not require the capping agent substitution step, yielding comparable efficiency to that containing pyridine as the surfactant [18,19]. As some metal complexes could be used as single source precursors for the preparation of such nanoparticles, the synthesis and investigation of the chemistry of new related metal complexes would be of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the Urbach's energy is 0.55 eV for P3HT and 0.43 eV for PPy. The high values of Urbach's energy compared to the previously reported one [63] may be an additional reason for lowering the band gap. The origin of Urbach's energy is a defect owing to the presence of impurities that create a localized state inside the band gap.…”
Section: Optical Propertiesmentioning
confidence: 63%
“…Table 1 shows an increase in the values of E u of the nanocomposites from 2197 meV, for sample C1, to be 2262 meV, for sample C3. This can be due to inducing disorders in PEDOT-PSS by the embedded Au NSs which appears in the band gap in the form of localized states depending on the size of Au NSs [24]. However, the observed low values of the Urbach energy of all nanacomposites compared to that of their hosting polymer (2566 meV) may be attributed to forming clusters by incorporating Au NSs [25].…”
Section: Optical Propertiesmentioning
confidence: 99%